The incidence of frailty and its relationship with long-term survival in patients with heart failure and implanted cardiac resynchronization therapy devices - A. M. Soldatova; V. A. Kuznetsov; D. S. Bogdanova; F. T. Benzineb (Российский кардиологический журнал)
Aim. To assess long-term survival depending on the presence and severity of frailty in patients with heart failure (HF) and implanted cardiac resynchronization therapy devices.Material and methods. We examined 77 patients (men — 74%, women — 26%, mean age 58,7±10,7 years) with NYHA class II-IV HF. The follow-up period was 42,4±27,1 months. On the basis of 31 parameters (medical history, diagnostic tests, questionnaire survey of physical activity limitations), a frailty index was calculated. Depending on the index value, the patients were divided into 2 groups: group 1 (n=41) — <0,375 (no frailty), group 2 (n=36) — ≥0,375 (patients with frailty).Results. Long-term survival of patients in group 1 was 87,8%, in group 2 — 52,8% (Log rank p<0,001). According to the univariate analysis, the presence of frailty was significantly associated with long-term mortality (odds ratio (OR) 6,108; 95% confidence interval (CI) 2,207-16,907; p<0,001). When sex, age, left ventricular ejection fraction, left bundle branch block, QRS duration, left ventricular volume were included in the multivariate analysis, the presence of frailty remained a significant predictor of long-term mortality (OR 5,763; 95% CI 1,837-18,083; p=0,003).Conclusion. Frailty has an independent effect on the long-term all-cause death risk in patients with HF and implanted cardiac resynchronization therapy devices.